KOH modification of fluorinated graphite and its reaction mechanism - Li, Hao; Hou, Genliang; Yuan, Xiaojing; Liu, Zhaohui; Luo, Weipeng; Song, Yongzhi; Bi, Song (Frontiers in Materials, 2022)
KOH electrochemical method and heating method were employed to modify ﬂuorinated graphite and explore the modification mechanism. The chemical composition and microstructure of the products were characterized and analyzed before and after the reaction. As the electrochemical reaction time or heating temperature increased, the carbon fluorine bond gradually underwent a nucleophilic reaction with KOH according to its reactivity, promoting the formation of fluorine ions in the residual product and carbon oxygen bonds in the corresponding oxidized fluorinated graphite (OFG). The electrochemical method with the anode on the bottom and the heating method were insufficient to allow the isolated carbon fluorine bond to react, retaining some carbon fluorine bonds. By positioning the anode on top, electron transfer significantly accelerates the activation of the carbon fluorine bond, which then reacts completely. According to theoretical simulation calculations, electronegative groups around the carbon fluorine bond can effectively enhance its reactivity.